Anayasa yargısının meşruluğu sorunu ışığında türk anayasa mahkemesi - Uslu, Ferhat (My University, 2008)
ANAYASA YARGISININ MEŞRULUĞU SORUNU IŞIĞINDA TÜRK ANAYASA MAHKEMESİ Halkın temsilcilerinden oluşan parlamentonun üzerinde, atama ile oluşmuş bir kurul tarafından yapılan yargısal denetimin meşruluğu, anayasallık denetiminin bulunduğu devletlerde tartışılabilir. Öncelikle, anayasa yargısının ve anayasa mahkemelerinin meşruluğu işlevlerinde aranmalıdır. Ancak, anayasa yargısının ve anayasa mahkemelerinin işlevleri de bu kurumların hukuksal ve demokratik meşruluğunu açıklamada yeterli olmayabilir. Anılan kurumların meşruluklarını güçlendirmek için; mahkemenin oluşumunda ulusal iradeye söz hakkı verilmesi, anayasa yargıçlarının görev süresinin belli bir süre ile sınırlandırılması, yurttaşlara bireysel başvuru hakkı tanınması, anayasa yargıçlarının rakip değerler ve siyasal kavramlar arasında bir tercih yapmayarak, bu işi seçilmiş otoritelerin yetkilerine bırakmaları, anayasa yargıçlarının denetimlerini daha çok demokratik sürecin işlerliğine yoğunlaştırmaları önerilmektedir. Türk Anayasa Mahkemesi’nin kuruluşunda ulusal iradeye rol tanınmadığı gibi, anayasa yargıçlarının görev süreleri de sınırlandırılmamıştır. Ayrıca Yüksek Mahkeme “anayasaya uygun yorum” yöntemini kararlarında çokça kullanmaktadır. Diğer taraftan, Türk yurttaşlarına bireysel başvuru hakkı tanınmamıştır. Türkiye’de Anayasa Mahkemesi’nin meşruluğuyla ilgili tartışmalar, ancak, yukarıda anılan önerilerin gerçekleştirilmesiyle giderilebilir.

TURKISH CONSTITUTIONAL COURT IN LIGHT OF THE ISSUE OF THE LEGITIMACY OF THE CONSTITUTIONAL REVIEW The legitimacy of judicial review by a committee constituted through an appointment over parliament consisting of people’s representatives may be argued in the states where the constitutional supervision exists. First, the legitimacy of constitutional review and constitutional courts should be sought at their functions. However, the functions of the constitutional review and constitutional courts may not be sufficient to explain their legal and democratic legitimacy. In order to strengthen the legitimacy of the above-mentioned institutions, the followings are suggested; to recognize national will in the formation of the court, to limit the term of the judges at the constitutional court with a specific term, to recognize the right to individual application of citizens, to leave the task of preference between rival values and political concepts to the elected authorities, to focus their supervision mainly on the operability of the democratic process. National will did not take an active role in the establishment of the Turkish Constitutional Court and neither were the terms of the constitutional judges limited. Furthermore, the method of “implementation according to the constitution” has been largely used by the Supreme Court. On the other hand, the right to individual application of Turkish citizens has not been recognized. The arguments over the legitimacy of the Constitutional Court in Turkey, however, can be overcome through fulfilling the above-mentioned suggestions.
Keywords: Anayasa; Anayasa Mahkemesi; Hukuk; Kamu Hukuku